2014
DOI: 10.5392/jkca.2014.14.05.085
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Analysis of the Movie Reviews

Abstract: Th i ss t u d y e x a mi n e dt h ec h a r a c t e r i s t i c so fmo v i er e v i e wsb a s e do ne mo t i o n a le x p r e s s i o n s , u s i n gt h es t r u c t u r a la n a l y s i s .Ma j o rr e s u l t swe r ea sf o l l o ws ;f i r s t l y ,t h emo s tc i t e de mo t i o n a l e x p r e s s i o n wa s' f u n ' .F u n wa st h ei mp o r t a n td i s c r i mi n a t o rf o re v a l u a t i n g mo v i e s .S e c o n d l y , c l u s t e ra n a l y s i sr e s u l t sf o u n dt h a ta l t h o u g hKo r e a nmo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Among previous studies and recommendation systems that use sentiment analysis, one study proposed a movie recommendation system by extracting emotion-related words from user reviews and comments to recommend personalized movies to individuals. In another study, the possibility of recommending appropriate movies to users was demonstrated through analysis of the sentiments of emotion-related words extracted from the sentiment lexicon, SentiWordNet [17]. Another study defined a review ontology, which is an emotion word dictionary for movies, to evaluate the sentiments of ratings and reviews [18].…”
Section: Recommendation System Using Sentiment Analysismentioning
confidence: 99%
“…Among previous studies and recommendation systems that use sentiment analysis, one study proposed a movie recommendation system by extracting emotion-related words from user reviews and comments to recommend personalized movies to individuals. In another study, the possibility of recommending appropriate movies to users was demonstrated through analysis of the sentiments of emotion-related words extracted from the sentiment lexicon, SentiWordNet [17]. Another study defined a review ontology, which is an emotion word dictionary for movies, to evaluate the sentiments of ratings and reviews [18].…”
Section: Recommendation System Using Sentiment Analysismentioning
confidence: 99%
“…3, June 2021 : 2399 -2406 2400 information accurately reflects the user"s preferences are raised, users are paying attention to the recommendation system that uses user-written product review data. In fact, research has shown that user"s text review plays an important role in building recommendation system [9][10][11][12][13][14]. Under these influences, research on analyzing product review data and reflecting it in the recommendation system is being actively conducted [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Under these influences, research on analyzing product review data and reflecting it in the recommendation system is being actively conducted [15][16][17][18][19][20]. Recently, research on emotional reviews of products and combining them with recommendation systems have been actively conducted [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%